The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/jcm9061908
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Wideband Absorbance as a Test for Otosclerosis

Abstract: The purpose of this study was to investigate the effectiveness of wideband energy absorbance in diagnosing otosclerosis by comparing the differences in acoustic absorbance between otosclerotic and normal ears. Exactly 90 surgically confirmed otosclerotic ears were included in the test group. The control group consisted of 126 matched normal-hearing subjects. The Titan hearing test platform (Interacoustics) was used for absorbance and acoustic immittance tests. Energy absorbance, measured at tympanometric peak … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
0
4
2
Order By: Relevance
“…These findings are very similar to what has been found previously and have an identical absorbance pattern. However, the reported frequencies of maximum absorbance are not exactly consistent across studies and are reported to be anywhere between 2000 and 4000 Hz [16][17][18]. A few studies have shown other maxima in the region of 1000 Hz to 1500 Hz [16,19], whereas the present study found maximum absorbance at 2000 Hz.…”
Section: Discussioncontrasting
confidence: 87%
“…These findings are very similar to what has been found previously and have an identical absorbance pattern. However, the reported frequencies of maximum absorbance are not exactly consistent across studies and are reported to be anywhere between 2000 and 4000 Hz [16][17][18]. A few studies have shown other maxima in the region of 1000 Hz to 1500 Hz [16,19], whereas the present study found maximum absorbance at 2000 Hz.…”
Section: Discussioncontrasting
confidence: 87%
“…The test is highly effective, with a sensitivity and specificity of more than 85%. 20 In the present study, pressurized acoustic absorbance at 630 Hz can differentiate the control group from the presurgery group and the pre from the postsurgery group (►Table 2).…”
Section: Discussionmentioning
confidence: 53%
“…The cited studies, however, were conducted only at ambient pressure, that is, without pressurization; only more recent studies analyzed pressurized WBT in otosclerosis. 20,21 Analyzing acoustic absorbance at peak pressure can enhance its diagnostic value in disorders of the middle ear. The present study aims to map the amount of energy transferred to the system using wideband frequencies under ambient pressure and pressurized conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The wide frequency range of the measurement renders it more independent from the external interference, making the test more accurate in assessing the middle ear pathology in adults compared with the classical tympanometry [20,27,28]. This method also allows for the measurement of absorbance without changes in pressure exerted on the tympanic membrane, making it extremely useful in examining tympanic membrane perforation, postoperative evaluation, after insertion of a transtympanic drain, and in the diagnosis of otosclerosis [29]. were compared.…”
Section: Resultsmentioning
confidence: 99%